Male reproductive system - Al-Juhaishi, Mohammed Abdulrazzaq Assi; Mohd Noor, Mohd Hezmee; Haron, Abd Wahid; Mohd Yusoff, Md Sabri; Rajion, Mohamed Ali (Universiti Putra Malaysia Press, 2017)
The overall reproductive process consists of both the human sex organs which include the male and female reproductive system. The ability to produce off springs that have similar characteristic as their parents is the goal of reproduction. The sexual type of reproduction takes place in human and both male and female reproductive system is required. Male reproductive system is mainly concerned with production of semen (whitish viscous fluid emitted from the male reproductive tract that contains sperm and fluids) and transferring it into the female reproductive tract. In this review, we will discuss the latest findings in the research pertaining the male reproductive system and its contribution towards the research in advancement of reproductive physiology.